THE USE OF TALKING STICK METHOD FOR STUDENTS' SPEAKING SKILL AT SMK AL-HUSEN PADEMAWU - Muhammad Darrin Zuhri (The Ellite of Unira, 2026)
This research has three research focuses, namely first, how the use of the talking stick method affects students' speaking skills, second, how students respond to using the talking stick method. This type of research uses qualitative research, which is explained descriptively. The data source is class XI students. The data collection procedures involve structured and unstructured interviews, participatory observation, and documentation. And data analysis was carried out to obtain the number of research findings. Meanwhile, checking the validity of the data was carried out using triangulation techniques. The results of this research show that: first, the application of the Talking Stick method to the speaking skills of class Second, the students' response after using the Talking Stick method in English speaking skills was very good because the students were happy and enthusiastic in the learning process, and the students also dared to speak in front of their friends. Keywords: talking stick method, speaking skill, English